A Web‐based tool for personalized prediction of long‐term disease course in patients with multiple sclerosis. Issue 7 (7th December 2012) - Galea, I.; Lederer, C.; Neuhaus, A.; Muraro, P. A.; Scalfari, A.; Koch‐Henriksen, N.; Heesen, C.; Koepke, S.; Stellmann, P.; Albrecht, H.; Winkelmann, A.; Weber, F.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose The Evidence‐Based Decision Support Tool in Multiple Sclerosis (EBDiMS) is the first Web‐based prognostic calculator in multiple sclerosis (MS) capable of delivering individualized estimates of disease progression. It has recently been extended to provide long‐term predictions based on the data from a large natural history cohort. Methods We compared the predictive accuracy and consistency of EBDiMS with that of 17 neurologists highly specialized in MS. Results We show that whilst the predictive accuracy was similar, neurologists showed a significant intra‐rater and inter‐rater variability. Conclusions Because EBDiMS was consistent, it is of superior utility in a specialist setting. Further field testing of EBDiMS in non‐specialist settings, and investigation of its usefulness for counselling patients in treatment decisions, is warranted.